Muscarinic receptor binding activity of polyoxygenated flavones from Melicope subunifoliolata - Chung, L.Y.; Yap, K.F.; Mustafa, Mohd Rais; Goh, S.H.; Imiyabir, Z. (Elsevier, 2008)
The bark extract of Melicope subunifoliolata (Stapf) T.G. Hartley showed competitive muscarinic receptor binding activity. Six polymethoxyﬂavones [melibentin (1);melisimplexin(3);3,30,40,5,7pentamethoxyﬂavone(4);melite rnatin (5); 3,5,8-trimethoxy-30,40,6,7 bismethylenedioxyﬂavone (6); and isokanugin (7)] and one furanocoumarin [5-methoxy-8-geranyloxypsoralen (2)]were isolated fromthe bark extract. Compounds 2 and 6 were isolated for the ﬁrst time from M. subunifoliolata. Themethoxyﬂavones (compounds 1, 3, 4, 5, 6, and 7) show moderate inhibition in a muscarinic receptor binding assay, while the furanocoumarin (compound 2) is inactive. The potency of the methoxyﬂavones to inhibit [ 3 H]NMS-muscarinic receptor binding is inﬂuenced by the position and number of methoxy substitution. The results suggest these compounds are probably muscarinic modulators, agonists or partial agonists/antagonists.